Study on the Household Use of Iodised Salt in Sindh and Punjab Provinces, Pakistan: Implications for Policy Makers - Gul Nawaz Khan; Imtiaz Hussain; Sajid Bashir Soofi; Arjumand Rizvi; Zulfiqar A. Bhutta (Journal of Pharmacy and Nutrition Sciences, 2012)
Purpose: To assess knowledge, attitude and practices with respect to use of iodised salt, and to estimate its uptake at household level in Sindh and Punjab, Pakistan. Methods: A cross sectional survey was conducted between January and March 2007. A structured questionnaire was administered and household salt tested for iodine content across 9,701 households to identify current knowledge and practices towards use of iodised salt. Results: Nearly 85% of the salt tested had no iodine, 8% had iodine levels of at least 75 ppm, whereas 7% of the salt contained between 15 and 50 ppm of iodine.The results of multivariate logistic regression analysis revealed that in comparison to urban areas, rural households were more likely not to use of iodised salt (adjusted odds ratio (AOR) =1.38, 95% CI 1.16-1.62), and Province Sindh was less likely not to use of iodised salt as compare to Punjab (AOR =0.81, 95% CI 0.69-0.96). In addition, results also revealed that illiteracy (AOR =1.61, 95% CI 1.28-2.04), no knowledge of iodised salt (AOR =2.09, 95% CI 1.44-3.04), unavailability of iodised salt (AOR =2.93, 95% CI 2.10-4.07), and unawareness about the advantages of use of iodised salt (AOR =1.97, 95% CI 1.65-2.36) were the main associated factors with non-use of iodised salt for cooking at household levels in Sindh and Punjab provinces, Pakistan. Conclusions: Despite awareness of iodised salt,actual use of adequately iodised salt was much lower, hence collaborative efforts between public and private sectors are strongly recommended to increase the availability and salt iodization in Pakistan.